A mixed methods evaluation of family-driven care implementation in juvenile justice agencies in Georgia - Kaitlin N. Piper; Alexandra Jahn; Cam Escoffery; Briana Woods-Jaeger; Amy Nunn; David P. Schwartz; Cathy Smith-Curry; Jessica Sales (BMC, 2024)
Abstract Background Improving family engagement in juvenile justice (JJ) system behavioral health services is a high priority for JJ systems, reform organizations, and family advocacy groups across the United States. Family-driven care (FDC) is a family engagement framework used by youth-serving systems to elevate family voice and decision-making power at all levels of the organization. Key domains of a family-driven system of care include: 1) identifying and involving families in all processes, 2) informing families with accurate, understandable, and transparent information, 3) collaborating with families to make decisions and plan treatments, 4) responding to family diversity and inclusion, 5) partnering with families to make organizational decisions and policy changes, 6) providing opportunities for family peer support, 7) providing logistical support to help families overcome barriers to participation, and 8) addressing family health and functioning. FDC enhances family participation, empowerment, and decision-making power in youth services; ultimately, improving youth and family behavioral health outcomes, enhancing family-child connectedness, and reducing youth recidivism in the JJ setting. Methods We evaluated staff-perceived adoption of the eight domains of FDC across detention and community services agencies in the state of Georgia. We collected mixed methods data involving surveys and in-depth qualitative interviews with JJ system administrators, staff, and practitioners between November 2021- July 2022. In total, 140 individuals from 61 unique JJ agencies participated in surveys; and 16 JJ key informants participated in qualitative interviews. Results FDC domains with the highest perceived adoption across agencies included identifying and involving families, informing families, collaborative decision-making and treatment planning, and family diversity and inclusion. Other domains that had mixed or lower perceived adoption included involving families in organizational feedback and policy making, family peer support, logistical support, and family health and functioning. Adoption of FDC domains differed across staff and organizational characteristics. Conclusions Findings from this mixed methods assessment will inform strategic planning for the scale-up of FDC strategies across JJ agencies in the state, and serve as a template for assessing strengths and weaknesses in the application of family engagement practices in systems nationally.